Barlyk Arasan at the Crossroads of the Turkic-Mongolian World - Sharip А.Ж.; Kishkenbayeva Ж.Қ. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
Barlyk-Arasan is a locality situated in the territory of the Urzhar District of the Abai Region, at the foot of the Arasantau Mountains, 18 kilometers northeast of the shores of Lake Alakol. The region is renowned for its thermomineral springs, which possess highly therapeutic properties. The area’s geological history, natural relief, climatic features, fauna, and flora have, to a significant extent, already been the subject of scientific research. Since the 1880s, following its inclusion under the jurisdiction of the Semirechye branch of the Red Cross Society, Barlyk-Arasan began to be mentioned in various sources as a balneological resort. In the traditional worldview of the local population, this region is regarded as a sacred space endowed with healing powers, capable of treating a wide range of ailments – from neurological and joint conditions to dermatological and gastrointestinal disorders. This article, employing cultural-linguistic and historical-comparative methods, explores the etymology of the toponym "Barlyk-Arasan" as well as the narrative structures of local oral legends associated with the area and historical figures embodying its collective memory (such as Genghis Khan, Galdan Tseren, Abylai Khan, and Kabanbai Batyr). The analysis reveals that the compound toponym “Barlyk-Arasan” translates as “a clayey, muddy place with healing mud and water,” and corresponds to ancient Turkic notions of the cult of mountains and the sacredness of water. Alternative etymological interpretations of the name are also taken into consideration. The research findings can contribute to the promotion of the spiritual heritage of Barlyk-Arasan and support the development of the cultural dimension of recreational tourism in the region.